Teaching russian phraseology with the component of color term “black” to philology foreign students - Chernova, Natalia (2021)
The study of phraseology is an advanced direction of teaching methods of Russian as a foreign language. Any non-native speaker embarking on a study of Russian is faced with the problems of understanding the phraseological units that the Russian language is replete with. Language learners experience particular difficulties when using phraseological units with the color designation component “black” in a real-life communicative situation. The problem of understanding the phraseology of the Russian language is associated with the fact that representatives of different countries have knowledge of the phraseology of their native language that encompasses regional geography, linguoculturological, national concepts, which often do not coincide with similar phenomena in the Russian environment. This paper scientifically substantiates the methodological system for working with phraseological units in the study of Russian as a foreign language. It presents a system of scientifically grounded assignments for foreigners to learn Russian as a foreign language.